A content analysis of the framing and representation of Black Lives Matter protests by South African mainstream media - Manyike, Lerato Gladys (Rhodes University, Faculty of Humanities, Department of Psychology)
This study conducted a detailed analysis of 277 headlines using content analysis, focusing on how News24 portrays racial protests, particularly within the Black Lives Matter (BLM) movement. It explored News24's coverage of BLM protests from March to December 2020, uncovering various framing strategies and language nuances in news headlines. The research aimed to identify thematic frames, linguistic patterns, and overall media framing of BLM protests. The findings highlighted different framing strategies, including legitimising, conflict, and delegitimizing frames, along with the impact of descriptive language on audience perceptions. The study concluded that media framing is dynamic, responding to evolving events and public discourse, and provided recommendations for media transparency, diversity in newsrooms, media literacy, and ethical reporting. Future research suggestions include comparative analyses, audience reception studies, and policy impact assessments to deepen understanding and inform strategic interventions in media representations and public discourse on racial justice. Overall, the study contributes valuable insights into media framing practices and their impact on societal perceptions of racial justice issues.
Keywords: Black lives matter movement; Social movements -- South Africa; Race in mass media -- South Africa; Frames (Sociology); Race discrimination -- South Africa